Identification of The Concept Selection Method for Product Design and Development in The Manufacturing Industry - Wei Chan, Shiau; Zaman, Izzuddin; Fauzi Ahmad, Md; Yee Liew, Check (International Journal of Engineering and Technology, 2018)
Concept selection is the most critical aspect of the entire product development process. However, many industries are not aware of this, or they might not possess essential knowledge about concept selection. Thus, this study aims to identify the concept selection method used by a series of particular areas within the manufacturing industry. In this study, the researcher conducted interviews with six managers from various production areas in the manufacturing industry. Then, the obtained data were analyzed qualitatively. The concept selection methods used for product design and development in the manufacturing industry were found to be based on various factors, including orders received, building and evaluating prototypes, discussion among executives, market demand, trial and error and the market’s standard deviation. This study serves as a guideline to help managers to evaluate concepts in a more practical way.